2003
DOI: 10.1002/app.12678
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of benzoxazine‐based phenolic resins: Crosslinking study

Abstract: Modified novolac resins with benzoxazine rings were prepared. The synthetic method involved the preparation of 1,3,5-triphenylhexahydro-1,3,5-triazine as an intermediate that further reacts with the novolac resin. The catalytic effects of phenols, carboxylic acids, and Lewis acids on the benzoxazine ring-opening polymerization were shown. The curing behavior of the benzoxazine compounds and the thermal properties of the cured resin were studied, and the results indicated improved degradation behavior for flamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 16 publications
3
64
0
Order By: Relevance
“…In previous studies, we modified novolac resins with benzoxazine rings and investigated the curing behaviour and properties of the cured resins [9]. We showed that the presence of phenolic groups decreases the curing temperature of the benzoxazine-novolac resins.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In previous studies, we modified novolac resins with benzoxazine rings and investigated the curing behaviour and properties of the cured resins [9]. We showed that the presence of phenolic groups decreases the curing temperature of the benzoxazine-novolac resins.…”
Section: Resultsmentioning
confidence: 94%
“…The results of the burn tests are shown in Table 3. Our previous results [9] showed that high modification degree on novolac-benzoxazine systems causes a decrease in flame retardance and NB2 with 80% of benzoxazine moieties exhibit a V-1 grade. The same occurs in the present phosphorous-free resins such as NBH systems while all phosphorous-containing resins produce a V-0 material (NBI and NBIH systems).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The 1,3,5-triphenylhexahydro-1,3,5-triazine and methyl 10-undecenoate (UDM) were synthesized according to a reported procedures [31,32,33]. All solvents were purified by standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…1,3,5-triphenylhexahydro-1,3,5-triazine [21,22] was synthesized according to reported procedures. All solvents were purified and dried by standard methods.…”
Section: Methodsmentioning
confidence: 99%